Isolation and Identification of Sulphur Oxidizing Bacteria from Freshwater Fish Farm Soil - Kumar, N. Ranjit; Archana, K. K.; Basha, K. A.; Muthulakshmi, T.; Joseph, T. C.; Prasad, M. M. (Fishery Technology, 2018)
Sulphur oxidizing bacteria (SOB) are natural microflora in aquaculture farms that play a significant role in sulphur cycle. In this study isolation, characterization and sulphate ion production ability was carried out to assess the role of SOB in utilizing thiosulphate. Ninety six distinct morphological isolates of SOB were isolated from the freshwater fish farm soil employing six different isolation media. Subsequent dye reduction test revealed that 16 isolates on Thiobacillus aquaesulis medium, 12 isolates on T. denitrificans medium, 9 isolates on T. thioparus medium and 10 isolates on Thiothrix medium showed characteristic color change of the dye (bromo phenol blue). Eight sulphur oxidizing bacterial isolates (SOBA17, SOBA12, SOBA3, SOBA20, SOBD10, SOBD16, SOBD12 and SOBD14) were selected for further studies based on the pH reduction test. To screen the potential sulphur oxidising bacteria, medium was amended with sodium thiosulphate and the sulphate ion production ability of the isolates was measured spectrophotometrically. Bacterial isolate of SOBA17 (1.62 mg ml-1) showed maximum sulphate ion production, followed by SOBA20 (1.50 mg ml-1). The 16S rRNA sequencing revealed that the isolates belonged to Thiobacillus aquaesulis. The partially purified sulphur oxidase of SOBA17 in SDS-PAGE exhibited three consecutive protein bands of molecular weight 10, 17 and 30 kDa. The present study revealed that SOB has the capacity to utilize sulphur in its oxidized state to non-toxic sulphate. Further studies are needed to understand the diversity and role of these bacteria in sulphur dynamics in aquaculture farms.